Formulation, characterization, and antibacterial testing of cream supplemented with Aloe vera (Aloe vera L.) gel and Nutgrass (Cyperus rotundus L.) rhizome ethanol extract - Mulyani, Sri; Rahmadina, Salsabila Adzani; Susanti VH, Elfi; Ariani, Sri Retno Dwi; Utomo, Suryadi Budi; Wathon, Muhammad Hizbul (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Various brands and forms offer a wide array of cream-based cosmetic products. However, only some of these products meet safety specifications. Aloe vera and nutgrass, two plants rich in bioactive compounds, possess anti-inflammatory, soothing, and antibacterial properties, making them ideal for health-safe cosmetic formulations. This research was conducted to develop antibacterial cream formulations incorporating these natural additives. The study focused on quality, organoleptic testing, and the formulated cream's antibacterial assessment. The research methodology encompassed several key processes: preparation of Aloe vera gel and nutgrass rhizome ethanol extract, formulation of the cream, quality testing by SNI 16-6069-1999 standards, organoleptic testing as per SNI 01-2346-2006, and antibacterial activity testing using Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922 bacterial strains. Results indicated that the cream formula enriched with Aloe vera gel and nutgrass rhizome ethanol extract meets the standards for skin-lightening creams and exhibits significant antibacterial capabilities. Furthermore, it was observed that the antibacterial effectiveness of the cream increases with the concentration of the nutgrass rhizome ethanol extract. These findings highlight the potential for integrating natural ingredients into modern cosmetic formulations, providing therapeutic and aesthetic benefits. This approach not only ensures compliance with safety standards but also leverages the natural properties of Aloe vera and nutgrass to enhance the product's functionality in skin care applications